THE RELATIONSHIP BETWEEN FAITH AND REASON IN JOHANNINE THEOLOGY: A BIBLICAL AFFIRMATION OF PRESUPPOSITIONAL APOLOGETICS - Peter Lillback (Verbum Christi: Jurnal Teologi Reformed Injili, 2014)
Through a study from biblical-theological perspective, that is a study of Johannine theology, the writer reconciles a classical controversy between faith and reason. The main question is whether the revelational propositions are discoverable only because God has spoken it or that man may also find those revelational propositions?through a philosophical exploration. Through the study of Johannine theology, the writer affirmed the significance of presuppositional apologetic.?